The Kabul Beauty School the art of friendship and freedom - Rodriguez, Deborah (London Sphere, 2014)
In a little beauty school in the war zone of Kabul, a community of women comes together, all with stories to tell. In the Kabul Beauty School, these women and many others find a safe haven and the seeds of their future independence.
On cover: "One little beauty salon. A community of women comes together".
UCWS-3290g donated by Adrienne Maguddayao - October 2018
Keywords: Kabul Beauty School; Beauty shops -- Afghanistan -- Kabul; Muslim women -- Afghanistan -- Kabul -- Social life and customs -- 21st century; Women -- Afghanistan -- Kabul -- Social life and customs -- 21st century; Manners and customs; Kabul (Afghanistan) -- Social life and customs -- 21st century